2023
DOI: 10.3390/jpm13030524
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cognitive Decline in Type 2 Diabetes Mellitus Patients: A Real-World Cross-Sectional Study in Mysuru, India

Abstract: The goal of this research is to study the prevalence of cognitive impairment in diabetes mellitus (DM) patients and establish the necessity of detecting and treating it early in these patients. A cross-sectional study was conducted at a tertiary care hospital in Mysuru for 4 months examined diabetic patients (test) and nondiabetic subjects (control) for cognitive decline using the Montreal Cognitive Assessment (MoCA) tool. Cognitive functions such as visuospatial/executive function, naming, attention, language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Type 2 diabetes may hasten the natural ageing process in several body systems, resulting in impairments. 19 It was observed in the current study that T2DM patients had lower MoCA scores 19 than non-diabetic subjects, which could be due to a longterm hyperglycaemic state in blood vessels, which could hasten neurodegenerative changes in the brain, thereby leading to cognitive impairment. In a study of 448 older adults, it was found that diabetes was linked to a more rapid decline in MMSE over a span of 9 years.…”
Section: Discussionmentioning
confidence: 70%
“…Type 2 diabetes may hasten the natural ageing process in several body systems, resulting in impairments. 19 It was observed in the current study that T2DM patients had lower MoCA scores 19 than non-diabetic subjects, which could be due to a longterm hyperglycaemic state in blood vessels, which could hasten neurodegenerative changes in the brain, thereby leading to cognitive impairment. In a study of 448 older adults, it was found that diabetes was linked to a more rapid decline in MMSE over a span of 9 years.…”
Section: Discussionmentioning
confidence: 70%
“…The model had a sensitivity of 78.57%, a specificity of 57.69%, a PPV of 66.67%, and a NPV of 71. 43 The area under the ROC curve for this model (Figure 1) was 0.701 (AUROC = 0.701, 95%CI: 0.559; 0.844, p = 0.011). In the cumulated population (Group A and B), the same probability can be estimated by the formula: exp(RS)/(1 + exp(RS)), where RS = 0.116+ 0.116 × (age) + 1.081 × (hyperlipemia), where hyperlipemia is 1 if the patient has hyperlipemia and 0 if the patient does not.…”
Section: Resultsmentioning
confidence: 82%
“…A study carried out in India that evaluated the presence of CD in diabetic patients by evaluating the MoCA concluded that its scores were statistically significantly lower in patients with DM-2 compared to those without ( p < 0.001). In patients with DM-2, MoCA assessment indicated the significant influence of age on CD ( p < 0.001) [ 43 ]. Another study following 3687 participants over 6 years, of whom 6.4% had DM-2, indicated that both MMSE and MoCA scores were lower in patients with DM-2 compared to those without.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in a cross-sectional study in Mysuru, India, patients with diabetes had a lower mean MoCa score than patients without diabetes (18.99±0.48 vs 26.21±0.46). However, this study excluded elderly patients (>60 years) and did not exclude patients with a prior diagnosis of cognitive impairment 17. In contrast, our study is unique as we demonstrate a previously unreported very high prevalence of severe cognitive impairment in elderly patients with diabetes and without a previous diagnosis of cognitive impairment.…”
Section: Discussionmentioning
confidence: 79%